Smart belt for the visually impaired to detect obstacles and track position - Jiadi, Naufal; Dewi, Citra; Hastuti; Ranuharja, Fadli (Journal of Industrial Automation and Electrical Engineering, 2024)
Mobility remains a significant challenge for individuals with visual impairments due to the difficulty in detecting obstacles around them. This study aims to design and develop a Smart Belt to assist visually impaired users by detecting obstacles and tracking their location in real time. The Smart Belt is equipped with a VL53L0X LiDAR sensor to detect frontal obstacles and a NEO-6MV2 GPS module for location tracking. Data collected from the sensors is processed by an ESP32 microcontroller and delivered to the user via a Telegram bot as notifications. Testing results indicate that the device is capable of accurately detecting obstacles and providing vibration alerts, while also successfully transmitting location coordinates to Telegram with satisfactory accuracy. This innovation is expected to enhance the independence and safety of visually impaired individuals in their daily activities